Testing sand strength with ring shear apparatus (Proceedings of Faculty of Civil Engineering, 2024)
This paper describes the determination of the shear strength parameters of sand using a ring shear apparatus (RSA). The paper presents the concept, the design of the apparatus and the test procedure in the apparatus, and offers the description of the soil sample. The tests were performed on samples of uniformly graded sand in drained conditions at normal effective stresses in the range of 32 to 200 kPa. The resistance of the seal inside the device itself was also taken into account. Consolidation was performed as part of the test, and then the sample was sheared with back pressure and a constant increase in shear displacement. Test results were used to determine the peak and residual parameters of the Mohr-Columb sand strength criterion.
Keywords: ring shear apparatus; effective normal stress; shear strength; residual strength; sand